Analisis Indek Kepuasan Masyarakat / IKM Di Rumah Sakit Umum Hasanuddin Damrah Manna Kabupaten Bengkulu Selatan - Triza Susana; Sulisti Afriani; Nurzam Nurzam (UNIVED Press, 2023)
At epoch of pandemi which now again world, health represent an elementary requirement to society. Requirement that's making society feel important to keep in good health and obtain;get service of health. These days society progressively aware of quality or quality service of health capable to give satisfaction [at] society itself. In a condition this time Hospital party/ side have have to know how quality of service of them can be accepted by its consumer, patient goodness take care of to lodge and also outpatient. Quality of service very closely related with cutomer/ client. Target doing/conducting of this research is to know analysis of indek satisfaction of society / IKM at home Common/ Public Pain of Hasanuddin Damrah Paradise Fruit Sub-Province of Bengkulu South. Type Research in this research is descriptive by wearing method research of Kusioner. While technique analyse data the used is by using measurement of value Make An Index To Satisfaction of Society / IKM pursuant to Regulation Of Minister Utilization Of State Aparatus And Reform Bureaucracy Republic Of Indonesia Number 14 Year 2017 About Guidance Of Compilation Of Survey Satisfaction Of Society Unit Organizer of Service of counted/calculated Public by using average value deliberated by the each service element. Result of this research can know that From 9 element service of society exist in common/ public hospital of Hasanuddin Damrah Paradise fruit, average value the got is equal to 3,09. Average value deliberated by at entire/all service element is 3,06. So that in earning conversion assess satisfaction of society exist in Common/ Public Hospital of Hasanuddin Damrah Paradise fruit is 76, 48 with quality of service